Clinical-radiographic correlates of Artery of Percheron infarcts in a case series of 6 patients. (March 2019) - Agarwal, Shashank; Chancellor, Breehan; Howard, Jonathan
Highlights: Bilateral paramedian thalamic infarcts lead to decreased level of consciousness. Rostral midbrain infarcts lead to oculomotor nerve palsies. Bilateral thalamic – midbrain infarction syndrome is suggestive of AOP infarction. Abstract: Bilateral thalamic strokes due to Artery of Percheron (AOP) occlusion are rare but have been previously reported in the literature. It is due to a rare anatomic variant where a solitary arterial trunk from the proximal segment of either posterior cerebral artery (PCA) supplies bilateral thalami and midbrain. Despite its description in the literature, these strokes are usually missed and patient's symptoms are not thought to be secondary to a vascular etiology. Through this report we aim to describe the clinical and radiographic features seen in these patients. We describe a series of 6 patients who present with varying levels of somnolence and oculomotor nerve palsies who had an occlusion of the AOP with bilateral thalamic infarcts with midbrain involvement. These clinical presentations, combined with the "V" sign on MRI are important in making the diagnosis.